Práticas pedagógicas inovadoras: narrativas sobre integração das tecnologias digitais da informação e comunicação no ensino superior - Vidal, Odaléa Feitosa (2015)
This study presents results of investigation about innovative teaching practices in higher education with the integration of Digital Tecnologies of Information and Communication (TDIC). The problem that guided this research refers to integration of TDIC in higher education, and if this represents innovative elements in pedagogic practice. It was defined as general objective to understand how the incorporation of these technologies in the pedagogical practice makes learning innovation in higher education. Moreover, specific objectives: Analyze criteria to defend the allocation of TDIC in pedagogical practice; making sense of innovation in teaching and learning; identify, from the perspective of teachers, innovative pedagogical practices and the benefits to the interaction relations established during the learning process. The thesis assumes that the integration of TDIC to pedagogical practices of professors in higher education bring innovative elements that modify these practices. The methodology used in the research was thematic oral history, divided into two stages: Selection of research subjects and interviews narratives of life stories and experiences of professors who teach and research in TDIC area in higher education in public and private educational institutions. The selection of ten (10) subjects was considered to be relevant to obtaining the results initially based on the reading of academic texts that approach learning with TDIC in education authored by subject narrators, followed by a screening by curriculum Lattes. The criteria adopted for the selection were: integration of TDIC in pedagogical practice, proven in scientific production and subjects taught; minimum of ten (10) years of teaching in higher education; research and teaching at the undergraduate and graduate levels; and interest to participate in the research. The categories adopted for the study were: (1) Worldview or digital culture; (2) Meeting with the world of TDIC; (3) Learning with TDIC; (4) Conceptions of educational and technological innovation; (5) Educational innovation with TDIC. The categories were interpreted based on the reflective attitude of the narrators about seemingly individual issues and implemented in the community. The narrative interviews were collected in person and online via Skype, in the period from March to July 2015, followed by transcription, processed and analyzed. Search results guided the new looks that recognize the subject of learning as the protagonist of the teaching process and learning, and it is up to the teacher the possibility of self-evaluation, reflection and reconstruction about the pedagogical practice.